2009
DOI: 10.1667/rr1677.1
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression in Primary Human Skin Keratinocytes and Fibroblasts in Response to Ionizing Radiation

Abstract: Although skin is usually exposed during human exposures to ionizing radiation, there have been no thorough examinations of the transcriptional response of skin fibroblasts and keratinocytes to radiation. The transcriptional response of quiescent primary fibroblasts and keratinocytes exposed to from 10 cGy to 5 Gy and collected 4 h after treatment was examined. RNA was isolated and examined by microarray analysis for changes in the levels of gene expression. Exposure to ionizing radiation altered the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 56 publications
3
36
1
Order By: Relevance
“…Strongly upregulated expression of the CDKN1A gene shown in this study slightly different from previous findings that showed only a several- or 10-fold increase in CDKN1A gene expression after radiation (from 4-fold to 10- or 50-fold or greater increase) [11,16,3538]. It is supposed that the difference of testing mode, primary design of CDKN1A gene composition and application of the primaries might be responsible for the diversity of the results.…”
Section: Discussioncontrasting
confidence: 99%
“…Strongly upregulated expression of the CDKN1A gene shown in this study slightly different from previous findings that showed only a several- or 10-fold increase in CDKN1A gene expression after radiation (from 4-fold to 10- or 50-fold or greater increase) [11,16,3538]. It is supposed that the difference of testing mode, primary design of CDKN1A gene composition and application of the primaries might be responsible for the diversity of the results.…”
Section: Discussioncontrasting
confidence: 99%
“…The predominant p53-elicited transcriptional response of hESC to IR exposures at early timepoint such as 2 hr resembles that observed in adult differentiated human somatic cells [11]. However, induction of p53 in pluripotent cells was shown to have some stem cell-specific consequences.…”
Section: Resultsmentioning
confidence: 95%
“…With the development of newer, high-throughput technology it became possible to interrogate the expression of thousands of genes simultaneously following specific treatment conditions [5], including genotoxic agent exposures [6]. These functional genomics experiments vastly extended our knowledge how human cells of different origins respond to IR [711]. DNA microarray profiling enabled identification of novel radiation-responsive signaling pathways, further advancing our understanding of IR effects on humans [12].…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression studies in human primary fibroblasts, keratinocytes (3638) and pulmonary epithelial cells (19) suggested that growth/differentiation factor 15 ( GDF-15 ), which is also a target gene of p53, is a radiation-responsive gene. Radiation-induced alterations in GDF-15 expression are correlated with the time and dose of radiation exposure (19,34).…”
Section: Introductionmentioning
confidence: 99%